Evaluasi Kinerja PLTMH Polohungo 40 KW Terhadap Small Scale Power Load (SSPL) - Steven Humena; Frengki Eka Putra Surusa; Amelya Indah Pratiwi; Rifat Kombu (Jurnal Teknik, 2021)
The Polohungo Micro-hydro Power Plant (PLTMH) in Polohungo village, Tolangohula District, Gorontalo Regency has several components, namely intake, headrace, forebay, tailrace, penstock, turbines, mechanical equipment systems, mechanical transmission systems, and generators. The increase of demand for electrical power and the limited capacity of the generator was causing suboptimal plant operation. This study aims to evaluate the performance of the 40 kW PLTMH against the electrical load in Polohungo Village, Gorontalo Regency. The evaluation stage began with the calculation of the technical parameter data of the equipment, which was then compared with parameters obtained from measurement. The evaluation results show that the overall condition of the main components such as generators, turbines, and the generator control system was still working well even though there was no history of maintenance. There was a power difference of 12.212 kW or 55.03% between the real-world generated power and theoretically calculated power based on turbine design water flow. Therefore, PLTMH Polohungo was not operating optimally when handling small-scale power loads, where the amount of power generated by theoretical calculations is greater than the amount of power generated when the generator is operating with a water flow rate of 0.02865 m3/second.